Physicochemical properties of absorbent hydrogel polymers in disposable baby diapers - Abd Manan T.S.B.; Beddu S.; Mohamad D.; Mohd Kamal N.L.; Itam Z.; Khan T.; Jusoh H.; Abdul Rahman N.A.; Mohamed Nazri F.; Mohd Yapandi M.F.K.; Wan Mohtar W.H.M.; Isa M.H.; et al. (Elsevier B.V., 2023)
Color; Computer software reusability; Fourier transform infrared spectroscopy; Physicochemical properties; Turbidity; Disposable baby diaper; Disposables; Fourier transform infra reds; Hydrogel polymers; Ph, turbidity, color; Physicochemical property; Sodium polyacrylates; Used diapers; WXRDF; X- ray diffractions; X ray diffraction